Revisión bibliográfica en un periodo de 10 años sobre habilidades motrices básicas en deportes (2021)
In the development of this research we analyze the research studies that have been carried out between the years 2010 – 2020 on basic motor skills in sports, this was done to identify the impact of sports practice on the development of basic motor skills. The analysis of research was done using the tool (RAI) developed in Excel by González Palacio, E. V. (2019), for data collection and statistical analysis, the collected data that was selected in categories were organized into an Excel table where comparisons were made and percentages of the data collected from this analysis were taken into conclusion that sports activities need to be implemented in school age as they favor positively the motor development of children, It was possible to identify through the search for research in the databases, that the most used test is the TGMD-2, since this is the most complete and objective when assessing basic motor skills, it can be concluded that the studies that used interviews, questionnaires or methods of observation , they have less scientific rigorousness in terms of the analysis of quantitative data, since these can be very subjective in the analysis of the results, the proposed objectives for the development of the work were met, since more than 50 research studies that talk about basic motor skills in sport were analyzed.